Edukasi Menopause Sehat bersama Ikatan Istri Dokter Indonesia (IIDI) Menuju Kehidupan Berkualitas - Uki Retno Budihastuti; Eriana Melinawati; Abdurahman Laqif; Asih Anggraeni; Affi Angelia Ratnasari (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
Menopause is a natural phase that every woman must experience, but it is often accompanied by various physical and emotional complaints that can interfere with daily life and reduce the quality of life. The lack of understanding and access to information makes most women unprepared to face this phase. The purpose of community service activities is to increase the knowledge and awareness of women aged 40 years or older about the concept of healthy menopause. The activity was carried out in a hybrid manner at the Auditorium of the Faculty of Medicine, Sebelas Maret University, involving obstetrics and gynecology specialists, health workers, and members of the IIDI Solo Branch. The implementation method includes counseling, interactive discussions, and evaluation through a pretest and a posttest. The results of the activity showed an increase in the average knowledge score of participants from 82.43 to 85.59, accompanied by an increase in awareness of the importance of early detection and handling of menopausal complaints. These findings confirm that sustainable education is an effective strategy to improve the quality of life of women in the lead-up to old age, in line with the goals of SDG 3, which emphasizes the importance of ensuring healthy lives and well-being for all ages.